Tea Drinking and Risk of Cancer Incidence: A Meta-Analysis of Prospective Cohort Studies and Evidence Evaluation. Issue 2 (1st October 2020) - Zhao, Long-Gang; Li, Zhuo-Ying; Feng, Guo-Shan; Ji, Xiao-Wei; Tan, Yu-Ting; Li, Hong-Lan; Gunter, Marc J; Xiang, Yong-Bing
ABSTRACT: Here we provide a comprehensive meta-analysis to summarize and appraise the quality of the current evidence on the associations of tea drinking in relation to cancer risk. PubMed, Embase, and the Cochrane Database of Systematic Reviews were searched up to June 2020. We reanalyzed the individual prospective studies focused on associations between tea drinking and cancer risk in humans. We conducted a meta-analysis of prospective studies and provided the highest- versus lowest-category analyses, dose-response analyses, and test of nonlinearity of each association by modeling restricted cubic spline regression for each type of tea. We graded the evidence based on the summary effect size, its 95% confidence interval, 95% prediction interval, the extent of heterogeneity, evidence of small-study effects, and excess significance bias. We identified 113 individual studies investigating the associations between tea drinking and 26 cancer sites including 153, 598 cancer cases. We assessed 12 associations for the intake of black tea with cancer risk and 26 associations each for the intake of green tea and total tea with cancer risk. Except for an association between lymphoid neoplasms with green tea, we did not find consistent associations for the highest versus lowest categories and dose-response analyses for any cancer. When grading current evidence for each association (number of studies ≥2), weak evidence was detected for lymphoid neoplasm (green tea), glioma (total tea, per 1 cup), bladder cancer (total tea, per 1 cup), and gastric and esophageal cancer (tea, per 1 cup). This review of prospective studies provides little evidence to support the hypothesis that tea drinking is associated with cancer risk. More well-designed studies are still needed to identify associations between tea intake and rare cancers.